2011
DOI: 10.5229/jecst.2011.2.2.063
|View full text |Cite
|
Sign up to set email alerts
|

Supercapacitive Properties of Carbon Electrode in an Electrolyte Containing a Newly Synthesized Two-Cation Salt

Abstract: :To examine the effects of a two-cation ionic liquid as an electrolyte component of a supercapacitor, 1,4-bis(3-methylimidazolium-1-yl)butane tetrafluoroborate (MIBBF 4 ), dissolved in propylene carbonate (PC) or acetonitrile (ACN), is newly synthesized and tested here for potential use as an electrolyte of capacitor. The MIBBF 4 salt exhibits higher ionic conductivity in ACN than in PC. The supercapacitive properties of capacitors containing an activated carbon electrode and various electrolytes are evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…It exhibits typical double-layer capacitive behaviour. It was also found that the cathodic and anodic charging currents increased with scan rates indicating that dependence of the capacitance on the scan rates and a pure capacitive behaviour (Cho et al, 2011). A high rate scan could stimulate large ohmic resistance distorting the CV loop hence resulted in a narrower loop with an oblique angle (Cheng et al, 2014).…”
Section: Methodsmentioning
confidence: 93%
“…It exhibits typical double-layer capacitive behaviour. It was also found that the cathodic and anodic charging currents increased with scan rates indicating that dependence of the capacitance on the scan rates and a pure capacitive behaviour (Cho et al, 2011). A high rate scan could stimulate large ohmic resistance distorting the CV loop hence resulted in a narrower loop with an oblique angle (Cheng et al, 2014).…”
Section: Methodsmentioning
confidence: 93%